Ours the experiment - Lozeau, Adam, author; Steensen, Sasha, advisor; Cooperman, Matthew, committee member; Howkins, Adrian, committee member (Colorado State University. Libraries, 2012)
Ours the Experiment is a poetry manuscript that examines topics of love, war, spirituality, and otherness. Consisting of five series, Ours the Experiment begins with the allegorical telling of the story of a nineteenth-century lynching. Its second series deals with love, loss, and loneliness, while also formally examining the influence of song and music on memory and storytelling. Its third series is an epithalamion, telling the history of a love that culminates in marriage and the story of the other loves nurturing and surrounding that relationship. Its fourth section examines the remnants of common biblical stories in both Western culture and in an individual mind, and its fourth section, "Going," is a single long poem chronicling a life-long friendship challenged by one man's choice to go to war. A poetic introduction and a collection of annotations of works influential in the writing of this manuscript are also included in this thesis.